1983
DOI: 10.1103/physrevlett.51.829
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Exchange Splitting in Ni Studied by Spin-Polarized Photoemission

Abstract: West GermanyAngle-and spin-resolved photoemission spectra from Ni(llO) have been measured in the temperature range 0.5^ T/T c^ 0.94. The data cannot be reconciled either with the predictions of local band theory assuming a temperature-independent exchange splitting or with a pure Stoner model. It is concluded that the exchange splitting decreases with increasing temperature and that spin fluctuations strongly influence the photoemission line shapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…8 The result of this procedure is shown in figure 4(b), for polarization vectors as indicated in figure 4(d). It can be noted that peak I 1 (k x ) is assigned a polarization vector P 1 ≈ (0, 1, 0) and therefore shows up only in the I ↑ y (k x ) spectrum, while I 2 (k x ) points almost in the opposite direction and shows up predominantly in the I ↓ y (k x ) spectrum.…”
Section: Analysis Of Spin-polarized Arpes Datamentioning
confidence: 99%
See 2 more Smart Citations
“…8 The result of this procedure is shown in figure 4(b), for polarization vectors as indicated in figure 4(d). It can be noted that peak I 1 (k x ) is assigned a polarization vector P 1 ≈ (0, 1, 0) and therefore shows up only in the I ↑ y (k x ) spectrum, while I 2 (k x ) points almost in the opposite direction and shows up predominantly in the I ↓ y (k x ) spectrum.…”
Section: Analysis Of Spin-polarized Arpes Datamentioning
confidence: 99%
“…The extra information contained in such spin-resolved spectra can provide very detailed information on exchange splittings and the magnetization state in magnetic systems [8], or in the case of surface states with strong spin-orbit interaction, on the splitting of Kramers pairs 5 [12], the degree of spin polarization of individual bands [13], and the detailed spin texture at the Fermi surface [14,15]. Moreover, the spin polarization provides an extra tag in such systems that permits to observe splittings smaller than the intrinsic width of the individual peaks that could not be resolved with regular ARPES [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight into this question has also been gained from photoemission and inverse photoemission experiments [6][7][8][9][10][11][12], and again conflicting views were obtained with respect to the temperature dependence of DE ex . Recent experiments found that spin-split bands merged with temperature at some k locations while their splitting remained temperature independent at others [10].…”
mentioning
confidence: 99%
“…Itinerant ferromagnetism in late transition metals at finite temperatures has been for a long time a subject of scientific debate [1]. Neutron scattering experiments [2] and also photoemission measurements on Ni [3,4] at high temperatures have in particular stimulated much discussion on the validity of the simple Stoner-Wohlfarth meanfield theory [5] which predicts the collapse of exchange splitting above the Curie temperature ͑T C ͒ and the disappearance of local moments. Observations of different k dependent exchange splitting behavior with temperature gave rise not only to fluctuating band theory [6] which assumes the persistence of a certain degree of short-range magnetic order above T C , but also to the two-pole ansatz plus effective medium approach for the Hubbard model [7] which predicts the retention of local moments above T C together with a collapse of the exchange splitting.…”
mentioning
confidence: 99%